Diagnósticos de Enfermagem em pacientes no pós-operatório mediato de transplante cardíaco e validação do diagnóstico considerado mais característico: angustia espiritual - Selme Silqueira de Matos (2009)
The first heart transplant in humans, pioneered by Barnard in 1967, represented thebeginning of important advances in the treatment of patients afflicted with terminalheart disease. This procedure went on to be considered a curative option fordiseases previously considered beyond therapeutic possibility. Nurses have soughtopportunities to develop their skills and technical-scientific competence to meet thedemands of this specialty and apply them with their patients. In both care andteaching practice with patients of the Transplant Program of the institutional field ofstudy, mainly in the post-operative phase, we came across a difficulty that had notbeen remedied until 2003 in the specific literature, which was the absence of anursing diagnostic profile and valid diagnosis for patients who had undergone a hearttransplant in all phases of this procedure. Faced with this gap to be explored, thisstudy aims to analyze the nursing diagnostic profile of post-operative hearttransplant patients, according to Taxonomy II of the NANDA and validate the mostcharacteristic diagnosis of this clientele. The study was developed in two steps: thefirst refers to a descriptive, exploratory, and retrospective study, developed throughthe evaluation of the nursing records contained in 49 files of patients who underwentheart transplants from 2003 to 2006 and who were in post-operative care (from 24hours to 10 days) to trace the profile of these patients and their nursing diagnoses.The second step was conducted with 54 nursing specialists in Intensive Therapy tovalid the diagnosis considered as the most characteristic of this clientele, usingFehring. A demographic and epidemiological profile was identified, consistingpredominantly of male adults, married, with incomplete elementary education,retired, Catholic, and from Belo Horizonte and other locations in Minas Gerais. Theprevailing disease was chagasic cardiomyopathy. Sixty (60) nursing diagnoses wereprepared and afterwards classified in 10 domains and 25 classes, according toTaxonomy II of the NANDA. The nursing diagnosis of spiritual distress was themost typical, according to nursing specialists, and its respective definingcharacteristics have been verified. Through validation, most of the definingcharacteristics obtained high scores (58.1%) and were classified as Very Pertinent(32.5%), Extremely Pertinent (25.6%), and Reasonably Pertinent (41.9%). Therewas no characteristic in the Somewhat Pertinent and Not Pertinent categories.The results of this study can assist in the planning of nursing interventions to bedesigned for this specific population.